Analyzing artificial intelligence in education with critical-constructive perspectives: The Vechta Venn - Lina Franken; Annekathrin Bock; Franco Rau (Medienimpulse)
Against the background of differing disciplinary understandings of AI in education, we suggest a theoretical framework – the Vechta Venn – as an analytical lens. The Venn informs theoretical discussion on AI in education and is applicable for empirical research. Drawing on contemporary research from educational sciences, media studies, and cultural studies and moreover identifying disciplinary overlaps, we introduce a rather theoretical-analytical approach than an empirically study on AI. In doing so, we follow a theoretical three-step of argumentation. First, we introduce the main lines of thought for each of the three disciplinary perspectives in their differences and specialties. Second, we focus on the intersections and overlapping of each pair of perspectives, respectively. Third, having outlined the respective synergies, we get to the core of the Venn, combining all three perspectives, interrogating the Venn’s applicability.